A comparison of persistence of SARS-CoV-2 variants on stainless steel. (August 2021) - Pottage, T.; Garratt, I.; Onianwa, O.; Spencer, A.; Paton, S.; Verlander, N.Q.; Dunning, J.; Bennett, A.
Summary: The survival of newer variants of SARS-CoV-2 on a representative surface has been compared to the established UK circulating isolate to determine whether enhanced environmental stability could play a part in their increased transmissibility. Stainless steel coupons were inoculated with liquid cultures of the three variants, with coupons recovered over seven days and processed for recoverable viable virus using plaque assay. After drying, there was no significant difference in inactivation rates between variants, indicating that there is no increased environmental persistence from the new variants.